The Necessity of General Collective Intelligence Driven Processes in Achieving Pervasive Manufacturing - Williams, Andy (My University, 2020)
General Collective Intelligence has been defined as a system that orchestrates groups to cooperate as a single collective intelligence that greatly increases the group’s general problem-solving ability. This increase in group problem-solving ability applies to any group problem. It applies to manufacturing, where GCI has the potential to facilitate decentralized processes not possible otherwise. It applies to design, where GCI has the potential to reliably enable groups to create designs far too complex otherwise. And it applies to cooperation in general, where GCI has the potential to enable cooperation to be reliably scaled, so where the value of that cooperation is positive and can therefore subsidize the cooperation itself, that value might be increased to the point that it can reliably create powerful competitive advantage for groups of local businesses that cooperate to supply local demand through pervasive manufacturing. This paper explores why for these and other reasons, GCI is a necessary component to achieving pervasive use of pervasive manufacturing.
Keywords: automation; future of work; General Collective Intelligence; pervasive manufacturing